Induced Hypertension for Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage: A Randomized Clinical Trial. Issue 1 (January 2018) - Gathier, Celine S.; van den Bergh, Walter M.; van der Jagt, Mathieu; Verweij, Bon H.; Dankbaar, Jan Willem; Müller, Marcella C.; Oldenbeuving, Annemarie W.; Rinkel, Gabriel J.E.; Slooter, Arjen J.C.; Algra, Ale; Kesecioglu, Jozef; van der Schaaf, Irene C.; et al.
Abstract : Background and Purpose—: Induced hypertension is widely used to treat delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage, but a literature review shows that its presumed effectiveness is based on uncontrolled case-series only. We here report clinical outcome of aneurysmal subarachnoid hemorrhage patients with DCI included in a randomized trial on the effectiveness of induced hypertension. Methods—: Aneurysmal subarachnoid hemorrhage patients with clinical symptoms of DCI were randomized to induced hypertension or no induced hypertension. Risk ratios for poor outcome (modified Rankin Scale score >3) at 3 months, with 95% confidence intervals, were calculated and adjusted for age, clinical condition at admission and at time of DCI, and amount of blood on initial computed tomographic scan with Poisson regression analysis. Results—: The trial aiming to include 240 patients was ended, based on lack of effect on cerebral perfusion and slow recruitment, when 21 patients had been randomized to induced hypertension, and 20 patients to no hypertension. With induced hypertension, the adjusted risk ratio for poor outcome was 1.0 (95% confidence interval, 0.6–1.8) and the risk ratio for serious adverse events 2.1 (95% confidence interval, 0.9–5.0). Conclusions—: Before this trial, the effectiveness of induced hypertension for DCI in aneurysmal subarachnoid hemorrhage patients was unknown because current literature consists only of uncontrolled case series. The results from our premature halted trial do not add any evidence to support induced hypertension and show that this treatment can lead to serious adverse events. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01613235.